PEMIKIRAN IBNU KHALDUN (PRAGMATIS-INSTRUMENTAL) TENTANG PENDIDIKAN DAN RLEVANSINYA DENGAN DUNIA PENDIDIKAN ISLAM KONTEMPORER - Fathiha, Nuril; Latipah, Eva; Sumedi (Jurnal Akademika Kajian Ilmu-Ilmu Sosial, Humaniora Dan Agama, 2023)
Preparing human resources who are religious and able to balance the pace of science with faith in the modern era is a fundamental problem in today's advanced era. Of course, the important role of education cannot be ignored in this process, because education is the main forum for development. This education can be obtained from studying more deeply and reflecting on the thoughts of classical Islamic figures. Ibn Khaldun is a figure in Islamic thought who is known as a philosopher, sociologist and historian. This writing uses a literature study method which aims to examine Ibn Khaldun's views on Islamic education which were influenced by many problems and realities of his time. The results obtained from this research are that Ibnu Khaldun's thoughts are very real and practical, without losing sight of the aim of developing students' potential. This is useful for providing opportunities for students to develop the potential that God has given them.